2000
DOI: 10.1080/00288233.2000.9513411
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for growth, puberty, and beef cow reproductive traits in a puberty selection experiment

Abstract: A selection experiment to change reproductive traits in Angus cattle has been maintained for 14 years, with first calvings in 1985. Alongside an unselected control line, three lines were established, selected for increased age at puberty in heifers (AGE+ line), reduced age at puberty in heifers (AGE-line), or increased scrotal circumference (SC line). The last two lines were merged at the 1992 matings, with the revised objective of applying further selection in both sexes to reduce age at puberty in heifers. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
60
3
12

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 16 publications
12
60
3
12
Order By: Relevance
“…In a selection experiment assessing change in reproductive traits in Angus cattle, Morris et al (2000) found that heritability of pregnancy rate was 0.04 for cows, 0.08 for 2-year olds and 0.12 for yearlings. Johnston and Bunter (1996) analysed calving success without adjustment for the categorical nature of the trait, and reported a heritability estimate of 0.11.…”
Section: Resultsmentioning
confidence: 99%
“…In a selection experiment assessing change in reproductive traits in Angus cattle, Morris et al (2000) found that heritability of pregnancy rate was 0.04 for cows, 0.08 for 2-year olds and 0.12 for yearlings. Johnston and Bunter (1996) analysed calving success without adjustment for the categorical nature of the trait, and reported a heritability estimate of 0.11.…”
Section: Resultsmentioning
confidence: 99%
“…En dicho estudio, los estimadores de heredabilidad para días abiertos fueron de 0,091 para vacas de diez o más partos y 0,197 para vacas de segundo parto. Por su parte, Morris et al (2000) reportaron que días abiertos fue 11% heredable en la raza Angus en un experimento de selección implementado para reducir la pubertad.…”
Section: Días Abiertosunclassified
“…Since 1984/1985, the herd had been used in a divergent selection study, with the breeding objective being to change AP in heifers (Morris et al, 2000). The herd consisted of a line selected for increased pubertal age (AGE1) and another for reduced pubertal age (AGE2); these two lines grazed alongside a control unselected line.…”
Section: Animalsmentioning
confidence: 99%
“…Studies over the last 20 years at AgResearch have established that age at puberty (AP) in grazing heifers is inherited (heritability 0.26 6 0.03, as reported by Amyes and Morris, 2009), and responses of various correlated traits to selection for lower AP have been reported, including growth (Morris et al, 2000), carcass (Morris et al, 2006) and reproduction Amyes, 2005 and. With the management constraints involved in running the selection experiment, which included mating dates being at about the same time each year (and similarly calving dates), the expression of puberty was confounded with season.…”
Section: Introductionmentioning
confidence: 96%